Parameters affecting calving difficulty of Charolais and Limousin breed at the Educational and Research Centre Logatec - Barbara KOTNIK; Nežika PETRIČ; Silvester ŽGUR (Acta Agriculturae Slovenica)
The aim of our study was to analyse parameters effecting calving difficulty of Charolais and Limousin cows at the Educational and Research Centre Logatec. Data from 492 calves, born between 1995 and 2006 were included in the analysis. We estimated calving difficulty with values from 1 to 3, where 1 meant easy calving (without or with minor help), 2 – difficult calving (at least 2 persons or veterinarian help), 3 – caesarean. Breed, sex of calves, parity, single or twin births, year of calving and birth weight had statistically significant effect on calving difficulty. In Charolais breed difficult calving occurred in 18.7% and in Limousin breed in 7.8%. Twins were associated with 4 times more frequent difficult calving than singles. First parity cows exhibited more frequent calving difficulty, whereas among other parities there were no statistically significant differences. The increased birth weight increased the possibility for difficult calving.